Enhancing Indigenous content in arts curricula through service learning with Indigenous communities - Bennett, Dawn; Bartleet, B.; Power, A.; Sunderland, N. (Australian Government Office for Learning and Teaching, 2014)
Executive summary At the heart of this project has been the desire to enhance the way in which Aboriginal and Torres Strait Islander cultural content is embedded in higher education arts curricula. It comes at a time when higher education institutions are facing growing pressure to make curriculum content more representative of and responsive to Aboriginal and Torres Strait Islander culture. In response, many Australian universities have established formal initiatives to embed Aboriginal and Torres Strait Islander culture and intercultural competency across the curriculum. This has taken the form of policies and reconciliation action plans, community engagement initiatives, networks and councils of Elders. Despite the proliferation of such initiatives, the incorporation of Aboriginal and Torres Strait Islander perspectives into higher education curricula and cultures remains a challenging political, social and practical task. This project has sought to address this challenging task by positioning arts based service learning (ABSL) as a strategy through which Australian higher education institutions can promote Aboriginal and Torres Strait Islander cultural content for students in ways that also directly support Aboriginal and Torres Strait Islander communities.